“Spiritual Armour”: Crafting Ukrainian Identity through Vyshyvanka (Czech Journal of International Relations, 2024)
The brightly coloured and delicately detailed “vyshyvanka”, the traditional Ukrainian embroidered shirt, has long been a marker of Ukrainian ethnic and cultural identity. In recent years in particular, the vyshyvanka has become an internationally recognized symbol of “Ukrainianness”; and yet despite its importance in Ukrainian identity-building and independence movements, remarkably little scholarship exists on this topic. This lack of academic engagement stems in part from twin forms of domination – colonial domination and gendered domination. Ukrainian history has often been overshadowed by Russo-centrism, while the significance of handicrafts practices such as embroidery has been dismissed because of their association with femininity and “women’s work”. Yet the sheer number of digital images of vyshyvanka and the proliferation of vyshyvanka-related designs in light of the full-scale Russian invasion of Ukraine in 2022, make this a topic worthy of our attention. In this article, I explore how and why the uses of vyshyvanka have evolved over time, charting differences in how the vyshyvanka has been depicted, and used, both by Ukrainians and by those seeking to denigrate or deny the existence of the Ukrainian nation. I focus in particular on the explosion of digital images featuring the vyshyvanka, which have been circulating since the Euromaidan of 2013-14, and on the history of the creation of World Vyshyvanka Day, now celebrated on the third Thursday of May and serving as a vehicle for mobilizing solidarity with Ukraine from Taiwan to the UK to Israel.
Keywords: vyshyvanka; Ukraine; identity; nationalism; euromaidan